HEAT – AND MASS TRANSFER EQUIPMENT DEVELOPMENT FOR POWER SYSTEMS (PART 2) - Doroshenko A. V.; Vasyutynsky S. Y. (Problems of the Regional Energetics)
The results of experimental investigations in film flow area in heat and mass exchangers are given. Values of critical number of Reynolds and average values of the liquid film thickness are adjusted. The special attention is given to the revelation of the optimal value the regular roughness of the surface, providing an intensification of heat and mass exchanging processes.It is possible to use the results which are obtained for designing heat – and mass exchangers in the refrigerate technique, air conditioning and generally, in power systems (alternative energetics).